Hepatokine leukocyte cell‐derived chemotaxin 2 as a biomarker of insulin resistance, liver enzymes, and metabolic dysfunction‐associated steatotic liver disease in the general population - Keita Suzuki; Hiromasa Tsujiguchi; Akinori Hara; Yumie Takeshita; Hisanori Goto; Yujiro Nakano; Reina Yamamoto; Hiroaki Takayama; Atsushi Tajima; Tatsuya Yamashita; Masao Honda; Hiroyuki Nakamura; et al. (Journal of Diabetes Investigation)
ABSTRACT Aims/Introduction Leukocyte cell‐derived chemotaxin 2 (LECT2) is an obesity‐associated hepatokine that causes skeletal muscle insulin resistance. Since LECT2 is up‐regulated by the inactivation of the energy sensor AMPK in the liver, we hypothesized that LECT2 has potential as a biomarker for metabolic dysfunction‐associated steatotic liver disease (MASLD). Therefore, we investigated whether circulating LECT2 levels are associated with insulin sensitivity, liver enzymes, and MASLD. Materials and Methods This cross‐sectional study included 138 Japanese individuals. Plasma LECT2 levels were measured using fasting blood samples. B‐mode ultrasonography was used to assess hepatic steatosis. Results The mean age and body mass index (BMI) of participants were 63.5 ± 10.2 years and 23.0 ± 3.1 kg/m2, respectively. Higher LECT2 levels positively correlated with homeostatic model assessment for insulin resistance (HOMA‐IR) values and negatively correlated with the quantitative insulin sensitivity check index (QUICKI) among all participants (HOMA‐IR; non‐standardized β (B) = 6.38, P < 0.01: QUICKI; B = −161, P < 0.01). These correlations were stronger in the low BMI group (HOMA‐IR; B = 13.85, P < 0.01: QUICKI; B = −180, P < 0.01). LECT2 levels also positively correlated with gamma‐glutamyl transferase levels (B = 0.01, P = 0.01) and alanine aminotransferase levels (B = 0.33, P = 0.02). Higher LECT2 levels correlated with the prevalence of MASLD (odds ratio = 1.14, P = 0.02). Conclusions The present results suggest the potential of plasma LECT2 levels as a biomarker for insulin resistance in individuals who are not overweight and the prevalence of MASLD in the general population.